The relationship between inflation and share price index in sri lanka - Amaresh, M. (Faculty of Management Studies and Commerce, University of Jaffna, Sri Lanka, 2019)
The stock market is playing a vital role in fostering the prosperity and economy of a country. Smooth functioning of a stock market will enable a country economically stabilized. The stock market has been functioning as one of the most vital components of a free-market economy, as it helps to arrange capital for the companies from shareholders. The stock market performance is measured by all share price index. The share price index is being affected by various factors but recently, inflation has become a dominant factor in destabilizing Sri Lankan economy. The sampling period of this study was from 1985 to 2016. The impact of inflation on share price index has been analysed in this research study. The inflation was considered as independent variable and All Share Price Index (ASPI) was considered as dependent variable. Hypotheses were tested using correlation and regression analyses. The research findings indicated that inflation significantly impacts on share price index. This paper investigates the relationship between inflation and share price index in Sri Lanka using time series data from 1985 to 2016 by employing correlation and regression analyses. Smooth functioning of a stock market will reduce stock market volatility which could potentially stabilize the economy and make it more efficient and prosperous. It has been widely observed by various researchers that there is relationship between inflation and all share price index, in Sri Lanka. The inflation is the independent variable and All Share Price Index (ASPI) is the dependent variable. The research findings indicated that the inflation significantly impacts on share price index in Sri Lanka.
Keywords: All Share Price Index; Inflation; Stock Market